Self-reported food allergies in early childhood in rural Australia - Weber, Heinrich C.; Bassett, Gaylene L.; Sohal, Sukhwinder S.; Prior, Sarah J. (Frontiers in Allergy, 2025)
IntroductionThe prevalence of childhood food allergies is escalating, with Australia notably affected. Research primarily originates from urban centres, leaving rural areas underrepresented. This study examines food allergy prevalence among 1,052 grade 1 and 2 children in regional and rural Tasmania.MethodDiagnosis relied on validated parental self-reports and identified anaphylaxis by symptoms coupled with breathing difficulties.ResultsThe median participant age was 8.1 years. Food allergy prevalence stood at 8.5% (n = 89), with cow's milk, peanuts/nuts, and eggs as primary allergens. Anaphylaxis prevalence was 18.0% (n = 16) of participants with food allergies, predominantly triggered by peanuts/nuts, eggs, and shellfish.ConclusionThe study delves into reactions to non-allergenic foods and associated avoidance leading to increased morbidity. This report contributes valuable insights to the insufficiently documented landscape of food allergy prevalence, shedding light on a poorly described aspect.